Bifidobacterium bifidum BGN4 Paraprobiotic Supplementation Alleviates Experimental Colitis by Maintaining Gut Barrier and Suppressing Nuclear Factor Kappa B Activation Signaling Molecules - Lee, So-Young; Lee, Byung-Hoo; Park, Jong-Hyun; Park, Myeong-Soo; Ji, Geun-Eog; Sung, Mi-Kyung (Journal of medicinal food, 2022)
Inflammatory bowel diseases, including Crohn's disease and ulcerative colitis, are characterized by chronic gastrointestinal inflammation with continuous relapse-remission cycles. This study aimed to evaluate the protective effect of BGN4 as a probiotic or paraprobiotic against dextran sulfate sodium (DSS)-induced colitis in mice. Ten-week-old female BALB/c mice were randomly divided into five groups. The control (CON) and DSS groups received oral gavage of PBS, whereas the live (LIVE), heat-killed BGN4 (HEAT), and lysozyme-treated BGN4 (LYSOZYME) groups received live BGN4, heat-killed BGN4, and lysozyme-treated BGN4, respectively, for 10 days, followed by DSS supply to induce colitis. The paraprobiotic (HEAT and LYSOZYME) groups had less body weight loss and colon length shortening than the DSS or LIVE groups. The LYSOZYME group exhibited better preserved intestinal barrier integrity than the LIVE group by upregulating gap junction protein expression possibly through activating NOD-like receptor family pyrin domain containing 6/caspase-1/interleukin (IL)-18 signaling. The LYSOZYME group showed downregulated proinflammatory molecules, including p-inhibitor of kappa B proteins alpha (I B ), cycloxygenase 2 (COX2), IL-1 , and T-bet, whereas the expression of the regulatory T cell transcription factor, forkhead box P3 expression, was increased. The paraprobiotic groups showed distinct separation of microbiota distribution and improved inflammation-associated dysbiosis. These results suggest that BGN4 paraprobiotics, especially lysozyme-treated BGN4, have a preventive effect against DSS-induced colitis, impacting intestinal barrier integrity, inflammation, and dysbiosis.